2012 American Control Conference (ACC) 2012
DOI: 10.1109/acc.2012.6314808
|View full text |Cite
|
Sign up to set email alerts
|

Nash strategy of multiparameter singularly perturbed Markov jump stochastic systems with state- and control-dependent noise

Abstract: This paper investigates Nash games for a class of multiparameter singularly perturbed stochastic systems governed by Itô's differential equation with Markov jump parameters with state-and control-dependent noise. First, in order to obtain Nash equilibrium strategies, cross-coupled stochastic algebraic Riccati equations (CSAREs) are introduced. After establishing an asymptotic structure with positive definiteness for solutions of CSAREs, feasible numerical algorithms by means of the linear matrix inequality (LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In order to overcome this inconvenience, in this work, we make the following assumption: Assumption The small parameters ϵ > 0, μ > 0 satisfy the condition lim(ϵ,μ)(0,0)δ=lim(ϵ,μ)(0,0)μ2ϵ=1. Remark Assumption is fulfilled, for example, if the parameters μ and ϵ satisfy a relation of the form μ = μ ( ϵ ) where μ :[0, ∞ )→[0, ∞ ) is a function with the properties: μ ( ϵ ) = 0 iff ϵ = 0. limϵ0+μ(ϵ)=0. limϵ0+μ2(ϵ)ϵ=1. A special case when the aforementioned conditions are fulfilled is μ(ϵ)=ϵ (see, e.g., ). On the other hand, in , limϵ0+μ2(ϵ)ϵ=0 is assumed. In this case, it should be noted that the asymptotic structure of the solution for , , , , , can be easily derived.…”
Section: Asymptotic Structure Of Coupled Stochastic Algebraic Riccatimentioning
confidence: 99%
See 4 more Smart Citations
“…In order to overcome this inconvenience, in this work, we make the following assumption: Assumption The small parameters ϵ > 0, μ > 0 satisfy the condition lim(ϵ,μ)(0,0)δ=lim(ϵ,μ)(0,0)μ2ϵ=1. Remark Assumption is fulfilled, for example, if the parameters μ and ϵ satisfy a relation of the form μ = μ ( ϵ ) where μ :[0, ∞ )→[0, ∞ ) is a function with the properties: μ ( ϵ ) = 0 iff ϵ = 0. limϵ0+μ(ϵ)=0. limϵ0+μ2(ϵ)ϵ=1. A special case when the aforementioned conditions are fulfilled is μ(ϵ)=ϵ (see, e.g., ). On the other hand, in , limϵ0+μ2(ϵ)ϵ=0 is assumed. In this case, it should be noted that the asymptotic structure of the solution for , , , , , can be easily derived.…”
Section: Asymptotic Structure Of Coupled Stochastic Algebraic Riccatimentioning
confidence: 99%
“…Because many applications of stochastic systems are governed by an Itô differential equation, the theory of optimal control and the related area for singularly perturbed and multi‐parameter stochastic systems has been well documented . These works have shown that there exists a parameter‐independent reduced‐order control that can achieve an arbitrary approximation of the optimal cost.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations